Isolation of Ribosome Particles from Meningopneumonitis Organisms - Tamura, Akira (1967)
In ribonucleic acid (RNA) extracted by phenol and sodium dodecyl sulfate from purified reticulate bodies of meningopneumonitis (MP) organisms, 21S, 16S, and 4S RNA were found by sucrose density gradient sedimentation analysis. When purified reticulate bodies were homogenized by sonic treatment or by treatment with sodium deoxycholate and were fractionated by differential centrifugation, more than 50% of the RNA was recovered in the fraction which was sedimented by centrifugation at 105,000 × g for 2 hr, but not at 13,000 × g for 20 min. From homogenates prepared in this manner, 50S and 30S particles containing RNA were isolated by sucrose density gradient centrifugation. These 50S and 30S particles were also found in lysates of cytoplasmic fractions of infected cells which were labeled by (32)P during 17 to 17.5 hr or 15 to 18 hr after infection. The synthesis of 50S and 30S particles was not inhibited by actinomycin D. When infected cells were homogenized in the presence of 0.01 or 0.02 m MgCl(2), 70S particles were isolated instead of 50S and 30S particles. When dialyzed against low concentrations of MgCl(2), the 70S particles dissociated to 50S and 30S particles. The base ratio of the 70S particles is very similar to that of 16S plus 21S RNA. The characteristics of the 70S, 50S, and 30S particles suggest that these are ribosome particles, similar to bacterial ribosomes.